2016
DOI: 10.1016/j.ifacol.2016.10.247
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Pulses to Control Bistable Monotone Systems Using Koopman Operator

Abstract: In this paper, we further develop a recently proposed control method to switch a bistable system between its steady states using temporal pulses. The motivation for using pulses comes from biomedical and biological applications (e.g. synthetic biology), where it is generally difficult to build feedback control systems due to technical limitations in sensing and actuation. The original framework was derived for monotone systems and all the extensions relied on monotone systems theory. In contrast, we introduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…4.3). Optimal control formulations have also been considered for switching problems [166,165,136]. Based on a global bilinearization, the underlying dynamical system can be stabilized using feedback linearization [65].…”
Section: Control Designmentioning
confidence: 99%
“…4.3). Optimal control formulations have also been considered for switching problems [166,165,136]. Based on a global bilinearization, the underlying dynamical system can be stabilized using feedback linearization [65].…”
Section: Control Designmentioning
confidence: 99%
“…In [4], [5], it has been proposed to solve the switching problem using temporal pulses of a fixed length τ and a fixed magnitude µ for monotone systems (cf. [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Applying linear stability analysis to establish global stability is one example (Mauroy and Mezic, 2013). Sootla et al (2016) leverage the Koopman operator in the design of temporal pulse control of bistable monotone systems. Brunton et al (2016) demonstrated the potential use of these operators to design optimal control laws for fully nonlinear systems using techniques from linear optimal control.…”
Section: Literature Review On the System Identification And Finite LImentioning
confidence: 99%
“…Sootla et al. () leverage the Koopman operator in the design of temporal pulse control of bistable monotone systems. Brunton et al.…”
Section: Introductionmentioning
confidence: 99%